Magnetic Microlassos for Reversible Cargo Capture, Transport, and Release - Yang, Tao; Tasci, Tonguc O; Neeves, Keith B; Wu, Ning; Marr, David W M (Langmuir, 2017)
Microbot propulsion has seen increasing interest in recent years as artificial methods that overcome the well-established reversible and challenging nature of microscale fluid mechanics. While controlled movement is an important feature of microbot action, many envisioned applications also involve cargo transport where microbots must be able to load and unload contents on command while tolerating complex solution chemistry. Here we introduce a physical method that uses flexible and linked superparamagnetic colloidal chains, which can form closed rings or "lassos" in the presence of a planar rotating magnetic field. By adding an additional AC magnetic field along the direction perpendicular to the substrate, we can orient the lasso at a tilted camber angle. We show that these magnetic lassos can roll at substantial velocities, with precise spatial control by manipulating both field strength and phase lag. Moreover, the lasso can curl around and capture cargo tightly and transport it based on a wheel-type mechanism. At the targeted destination, cargo is easily released upon field removal and the lasso can be readily reused. Since the entire process is physically controlled with no chemistry for attachment or disengagement involved, our system can potentially be used for transporting diverse types of cargo under different solution conditions.